Effect of Age and Season on the Fresh Semen Quality of Bali Bulls in Indonesia - Warman, Adi Tiya; Panjono; Sawitri, Wiwied; Wijanarko, Andi Widodo; Atmoko, Bayu Andri; Bintara, Sigit; Mastuti Widi, Tri Satya; Jannah, Zaenab Nurul; Baliarti, Endang (Agriculture and Natural Resources, 2025)
Importance of the work: Bali cattle are native to Indonesia. However, limited research exists on sperm quality variations across different ages and seasons. Objectives: To investigate how age, collection season, and their interaction impact the quality of fresh semen from Bali bulls in Indonesia. Materials and Methods: Data were collected from 353 ejaculates collected during the rainy and dry seasons from 15 Bali bulls divided into three age groups: pubertal, adult and senior. The evaluation was performed on fresh semen based on standard operating procedure in the Singosari National Artificial Insemination Centre (SNAIC). Two-way analysis of variance and Pearson correlation were used to determine the effect of age, season and the interaction between age and season on fresh semen quality. Data were analyzed using IBM SPSS Statistics for Windows (version 25; IBM Corp, 2017). Results: The findings revealed a significant interaction between age and collection season on sperm concentration (p < 0.05). Age significantly influenced semen pH, concentration, and abnormalities of sperm (p < 0.05), while the season affected semen volume, motility, concentration, and abnormalities of sperm (p < 0.05). A positive correlation was found between age with sperm concentration (0.42) and abnormality (0.15), but a negative correlation with semen pH (0.15). Additionally, the season was positively correlated with semen volume (0.18) and sperm abnormalities (0.24) but negatively correlated with motility (0.20) and concentration (0.11) of sperm. Main finding: Age, season, and their interaction significantly affect the quality of fresh semen from Bali bulls. For commercialization, it was found that bulls older than seven years were the best age because they had a higher sperm concentration. Meanwhile, cement collection is still recommended in both seasons because the potential production straw is the same based on semen volume and sperm concentration.